2017
DOI: 10.1007/s41782-017-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Hangover, Sleep Quality, and Daytime Sleepiness

Abstract: Purpose Heavy drinking has been shown to disrupt sleep, increase sleepiness the next day, and produce symptoms collectively referred to as ''hangover''. A survey was conducted to determine the impact of heavy alcohol consumption on sleep, daytime sleepiness, and hangover severity. Methods N = 335 adults, experienced with alcohol hangover, completed a survey of sleep quality, daytime sleepiness, and hangover symptoms comparing a heavy drinking occasion with a non-alcohol occasion. Data from those who reported [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
(12 reference statements)
7
15
2
Order By: Relevance
“…In addition, 37.9% scored >10 on the ESS indicating that a proportion of clients were experiencing high levels of daytime sleepiness. This is particularly important considering the negative consequences associated with daytime dysfunction, including falling asleep while driving (Ftouni et al, ; Reyner & Horne, ), and is consistent with previous research demonstrating that heavy alcohol consumption is associated with next day performance decrements (Rohsenow et al, , van Schrojenstein Lantman, Roth, et al, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, 37.9% scored >10 on the ESS indicating that a proportion of clients were experiencing high levels of daytime sleepiness. This is particularly important considering the negative consequences associated with daytime dysfunction, including falling asleep while driving (Ftouni et al, ; Reyner & Horne, ), and is consistent with previous research demonstrating that heavy alcohol consumption is associated with next day performance decrements (Rohsenow et al, , van Schrojenstein Lantman, Roth, et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…Links between heavy drinking and poor sleep have also been reported in college students (Miller et al, 2017) and adults (van Schrojenstein Lantman, Mackus, Roth, & Verster, 2017), with poorer sleep associated with extended and more severe hangover symptoms (van Schrojenstein Lantman, Mackus, et al, 2017) and increased next day sleepiness (van Schrojenstein Lantman, Roth, Roehrs, & Verster, 2017). Sleep has also been examined in outpatients following treatment for alcohol dependence (Currie, Clark, Rimac, & Malhotra, 2003;Foster & Peters, 1999) and may play a role in the development of a subsequent mood or psychiatric disorder (Roberts, Roberts, & Duong, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hangover was reliably induced by using a semi-naturalistic study design and allowing participants to self-administer alcohol, according to the estimated BAC calculations, participants obtained a mean eBAC of 0.135%, a level beyond that deemed required to cause a hangover [1,50]. Self-reports also provided support for the link between hangover and poor sleep quality [16,51,52]. However, our findings were inconsistent with previous sleep studies that show a faster sleep onset after alcohol [53][54][55].…”
Section: Discussioncontrasting
confidence: 66%
“…The number of smoked cigarettes was recorded as well, as previous research has shown an interaction between smoking and hangover [18]. To capture possible effects of sleep [14,19,20], total sleep time was recorded as well as the (consciously perceived) number of nightly awakenings. Sleep quality was rated on an 11-point scale ranging from 0 (very poor) to 10 (excellent) [21,22].…”
Section: Data Collectionmentioning
confidence: 99%